Improving Public Service Quality: Analyzing the Impact of Simpelmi Online Application in Sinjai Regency - Sukmawati, Sukmawati; Hermansyah, Hermansyah; Takdir, Muhammad (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This research aims to analyze the impact of the SIMPELMI online application on improving public service quality in Sinjai Regency. The research used a qualitative method and data collection techniques such as literature study and descriptive analysis in data analysis. The findings showed that the SIMPELMI application has had a positive impact on improving public service quality in Sinjai Regency, although there are still issues such as service issues that are not based on uniform service standards, complex licensing application processes, and inadequate human resources. The study suggests that improving the service quality of the SIMPELMI application can be done by addressing these issues and providing continuous training and development for human resources. Overall, the SIMPELMI online application has great potential to improve public service quality in Sinjai Regency.